2019
DOI: 10.1097/or9.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence, distress, depressive symptoms, and quality of life in hematopoietic stem cell transplantation patients

Abstract: Background: Symptoms of psychological distress, including fear of cancer recurrence (FCR) and quality of life (QOL) deficits are common along the hematopoietic stem cell transplantation (HCT) survivorship trajectory. Identifying patterns over time could contribute to timely interventions. Materials and Methods: HCT recipients completed the Distress Thermometer (DT), the Center for Epidemiologic Studies-Depression scale (CES-D), the Fear of Relapse and Recurrence Scale, and the Functional Assessment of Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Our DLC intervention began on day −5 of SCT, which preceded hospital admission for high-dose chemotherapy by 2-3 days. Our rationale for this time frame was to focus on the acute posttransplant period itself, a time during which QOL is known to decrease because of increased symptom burden and acute life disruptions [ 11 - 15 ]. However, in contrast to 2 prior studies that demonstrated that distress peaked at count nadir or hospital discharge [ 3 , 15 ], this study found that elevated distress was highest at pre-SCT baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our DLC intervention began on day −5 of SCT, which preceded hospital admission for high-dose chemotherapy by 2-3 days. Our rationale for this time frame was to focus on the acute posttransplant period itself, a time during which QOL is known to decrease because of increased symptom burden and acute life disruptions [ 11 - 15 ]. However, in contrast to 2 prior studies that demonstrated that distress peaked at count nadir or hospital discharge [ 3 , 15 ], this study found that elevated distress was highest at pre-SCT baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Our rationale for this time frame was to focus on the acute posttransplant period itself, a time during which QOL is known to decrease because of increased symptom burden and acute life disruptions [ 11 - 15 ]. However, in contrast to 2 prior studies that demonstrated that distress peaked at count nadir or hospital discharge [ 3 , 15 ], this study found that elevated distress was highest at pre-SCT baseline. As a second observation of note, our narrow pre-SCT window also precluded participation for 1 of our 15 enrolled patients who was unable to connect with her coach before hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer development and progression, as well as TCT treatment, alter innate and adaptive immune function (12). The significant stress associated with a cancer diagnosis, treatment, and accompanying life disruption can also adversely affect immune function (13,14). Specifically, stress and adverse psychosocial factors alter neural and endocrine pathways that ultimately affect gene regulation in immune cells (15)(16)(17)(18)(19).…”
Section: Biobehavioral Processes In Tctmentioning
confidence: 99%
“… 3 , 4 At present, the risk of cancer recurrence is a significant factor affecting HSCT survivors. 5 , 6 For example, previous studies have shown that the incidence of FCR in HSCT survivors is about 50%–90% 5 , 7 , 8 being more severe among survivors who are 55 years old and younger compared with those older than 55 years. 8 However, none of these studies described specific details of the adolescent and young adult (AYA) age group who underwent HSCT.…”
Section: Introductionmentioning
confidence: 99%